PEDAGOGICAL FOUNDATIONS OF MORAL EDUCATION OF PRIMARY STUDENTS BASED ON FOLK ORAL CREATIVITY (World Bulletin of Education and Learning, 2025)
The article highlights the theoretical and practical aspects of using examples of folk oral literature in the moral education of primary school students. It analyzes the role of fairy tales, proverbs, riddles, and other folklore genres in developing qualities such as kindness, honesty, and diligence in children. The article also discusses the educational potential of folk literature, the age and psychological characteristics of students, and provides methodological recommendations for using folklore materials in classroom activities.
Keywords: Folk oral literature, primary education, moral upbringing, pedagogical methods, folklore, child psychology, educational process.